THE INTERPLAY OF SOCIAL SUPPORT, ACADEMIC STRESS, AND MENTAL HEALTH HELP-SEEKING AMONG UNIVERSITY STUDENTS - Yeop, Afiqah; Ho, Meng Chuan; Ooi, Pei Boon; Tan, Siew Tin (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
University students worldwide face increasing mental health challenges, yet disparities in help-seeking behaviour persist across cultural and social contexts. This study explores how different levels of perceived social support interact with academic stress and mental health help-seeking intentions among a diverse group of university students, with a focus on differences by nationality and gender. A cross-sectional survey of 259 students (55.2% female; 62.9% Malaysian, 37.1% non-Malaysian) assessed perceived social support (using the Multidimensional Scale of Perceived Social Support, MSPSS), academic stress, and mental health help-seeking behaviour. Results showed a significant relationship where students with moderate social support had lower help-seeking intentions compared to those with low (mean difference = 0.56, p = .002) or high support (mean difference = -0.44, p = .005). Malaysian students reported higher academic stress (mean difference = -0.13, p = .034) but lower help-seeking behaviour (mean difference = 0.34, p = .007) than their non-Malaysian peers, suggesting that cultural stigma may influence these effects. Gender differences were not significant. These findings challenge the belief that moderate social support is enough to promote mental health engagement and highlight the need for culturally tailored interventions in academic settings.